The prevalence of breast cancer in Africa and establishment of The Libyan Breast Cancer Registry - Abulkasim, Muna Abdussalam Owen (Department of Medicine, 2020)
Breast cancer is well-known globally and remains one of the principal health concerns affecting women, and a rare malignancy in men. Although, there has been significant progress made in prevention strategies such as early detection and better treatment in most developed countries, incidence and mortality rates of breast cancer continued to rise. The rise is significant in Africa, a continent low in resources with a growing and ageing population exposed to risk factors leading to developing the disease. Although the incidence of breast cancer is lower in Africa than in high-income countries, mortality rates are high, mainly in women less than fifty years of age. Like most African countries, Libya is least prepared to cope with breast cancer and cancer in general. Additionally, many Libyans are adopting unhealthy lifestyles together which, together with environmental changes and high life expectancy, is perhaps the cause of rising cancer rates. However, no systematic collection of breast cancer incidence is currently undertaken, which in turn, impacts the implementation of detection and treatment measures. This thesis sought to evaluate the situation of breast cancer in Africa and specifically, for Libyan patients, through a systematic review of prevalence studies in Africa and by designing a registry for Libyan breast cancer patients. Objectives : • To conduct a systematic review and literature-based meta-analysis to provide an evidence-based estimate of the prevalence rate of breast cancer in Africa. This systematic review provides epidemiological data to guide health practitioners, educators and researchers for further studies needed in the field of breast cancer, specific for African patients. • To design a breast cancer registry for Libyan breast cancer patients. Developing a Libyan breast cancer registry provides an opportunity to learn more about disease development, and the changes through the course of the patient's life. Secondly, we will be able to track the incidence, mortality, and survival of patients diagnosed with breast cancer and their distribution in Libya. Finally, the information will be translated into numbers to aid policymakers in measuring the extent of the problem and help researchers in taking action needed to reduce the breast cancer load in Libya. Methods: • A systematic literature search was performed to identify studies retrieved from electronic databases, grey literature and reference lists, with no time and language limits. We have reviewed the available studies addressing the prevalence rate of breast cancer for African patients living in Africa who developed the disease. • Secondly, the Libyan Breast Cancer Registry (LBCR) is a prospective, hospital-based registry planned to document clinical and imaging characteristics of patients at presentation. Through follow-up, we will document disease progression and treatment practices to reliably determine the incidence of all-cause mortality and worsening disease requiring hospitalization. Results: • The overall prevalence rate of breast cancer in Africa was 0.30 [ 95% CI, 0.26 to 0.34] (22 studies, n=10,795). The prevalence rate of breast cancer for African females was 0.49 [95% CI, 0.38 to 0.62]. South African region had the highest breast cancer prevalence rate, 0.65 [95% CI, 0.24 to 1.26], while the lowest rates of breast cancer were from Central African regions. The use of mammography yielded higher rates of detection, (0.63 [95% CI, 0.46 to 0.82]), in comparison with clinical breast examination (0.31 [95% CI, 0.22 to 0.42]). • The proposed LBCR comprises parts I, II, AND III. Part I consists of demographic data and cancer information detailing personal data such as medical history, general examination, breast examination, methods and results of the diagnosis, and the treatment offered. Part II comprises the forms used for continuous follow-up – a new form is completed at each visit. All new information regarding patients' details, new complaints, and investigation findings and any changes or treatment offered at the visit, are recorded in this section. Part III documents mortality information. Details are recorded accompanied with a copy of the death certificate, and an autopsy report in case it was required. The LBCR pack includes consent forms in both English and Arabic languages. Also, it is accompanied by a manual of operation with given answered examples. Furthermore, the form is provided with contact details in case of any required information or explanation needed in the future. Conclusion: The clinical picture of breast cancer in Africa differs from Western countries due to the high proportion of patients developing the disease at a younger age and seeking management care at an advanced stage. Currently, there exists no specific breast cancer registry designed specifically for any African patients living in Africa. The LBCR will provide comprehensive, contemporary data on patients with breast cancer through establishing a baseline figure of the current situation for future local and national comparisons. The LBCR includes ready and accessible information for the temporary and future use of medical elements and researchers in this field and will help in the development of strategies to prevent and manage breast cancer and its complications.